Clima laboral en el departamento de la ATM-B de la empresa Transvial-EP - Narváez Cotto, Ana de Jesús (2020)
The present case study contains relevant aspects regarding the work environment of the Babahoyo Municipal Transit Agency and how it affects the personnel who work within it. The investigation was carried out in the department of the Babahoyo Municipal Transit Agency, of the company TRANSVIAL-EP, after observing problems regarding leadership, communication and physical space within the Agency and how it negatively affects job performance of technical operational and administrative personnel. The work climate is essential within the company, it is considered as the column in staff relations, it allows the fulfillment of objectives and goals established in the company, since it allows working life to be more enjoyable and committed among the work team.